Effect of Gradation Variability on Volume Parameter and Key Performances of HMA - Liu, Shutang; Zhu, Lin; Zhang, Huiqin; Liu, Tao; Ji, Ping; Cao, Weidong (Frontiers in Materials, 2021)
The graded mineral aggregate composed of coarse aggregate, fine aggregate and mineral powder is the main component of hot asphalt mixture (HMA), and it occupies a mass ratio of more than 95% in HMA. The gradation variability of mineral aggregate is frequently an unavoidable problem in the construction of asphalt pavement engineering. In order to investigate the effect of gradation variability on the volume parameters and key performances of HMA, the asphalt concrete with nominal maximum particle size of 20mm (AC20) was selected as the research carrier. Firstly, a benchmark mineral aggregate gradation (BMAG) was designed based on the theory of dense skeleton gradation presented in the paper. Secondly，six types of HMA (that is AC20) with variable gradations were also determined and all the specimens were prepared by rotary compaction process with the same optimum asphalt content (Gradation varies but asphalt content remains the same.), and finally based on asphalt pavement analyzer (APA) the performances of all the specimens of each gradation were tested. The results show that, compared with the BMAG-HMA, the volume parameters such as air voids (AV), voids in mineral aggregate (VMA) and voids filled with asphalt (VFA) of the variable-graded HMA change in different directions, but the water stability and high-temperature performance both degrade greatly. The experimental results also show that the feasibility and effectiveness of the dense skeleton gradation design theory adopted in this study.